Prevalence of frailty among community-dwelling elderly persons in Spain and factors associated with it. (2nd October 2019) - Rivas-Ruiz, Francisco; Machón, Mónica; Contreras-Fernández, Eugenio; Vrotsou, Kalliopi; Padilla-Ruiz, María; Díez Ruiz, Ana Isabel; de Mesa Berenguer, Yolanda; Vergara, Itziar
Abstract: Background: For effective prevention and intervention, and reduction of dependency, it is essential to determine the presence of frailty in the community. Objectives: To describe the prevalence of frailty among elderly persons living independently, in two primary healthcare areas in Spain; to identify factors correlated with its presence. Methods: This descriptive cross-sectional study was conducted between May 2015 and July 2016 among non-institutionalized individuals aged ≥70 years living in the primary healthcare areas of Gipuzkoa and Costa del Sol (Spain). The main outcome variable was the prevalence of frailty (determined by modified Fried criteria). The independent study variables were sociodemographic characteristics, anthropometric data and health-related life habits. Results: The study population consisted of 855 individuals (53% women). The overall prevalence of frailty was 26.2% (Gipuzkoa 14.2%, Costa del Sol 38.0%). Using multiple logistic regression, the following factors were associated with frailty: female sex (OR: 1.98; 95%CI: 1.37–2.86); cumulative illness rating scale (OR: 1.05; 95%CI: 1.00–1.10); self-perceived health status (OR: 0.96; 95%CI: 0.95–0.97); self-perceived unhealthy lifestyle (OR: 3.37; 95%CI: 2.05–8.87); dissatisfaction with the domestic environment (OR: 2.11; 95%CI: 1.18–3.76); and cognitive impairment (OR: 4.10; 95%CI: 2.05–8.19). In the multivariable model, 'geographical area' differences persisted, with an OR of 3.51 (95%CI: 2.29–5.36) for the Costa del Sol area, using Gipuzkoa as reference. Conclusion: In this population of community-dwelling persons aged 70 years and over, the prevalence of frailty was 26%. Factors correlated with frailty were female sex, comorbidity, poorer self-perceived lifestyle and health status, and dissatisfaction with the domestic environment.